Fish-based groups for ecological assessment in rivers: the importance of environmental drivers on taxonomic and functional traits of fish Assemblages - Matono, Paula (2012)
The use of river-types is of practical value, serving as groups for which assessment procedures can be developed and applied. An abiotic typology was set by the Portuguese Water Agency, mainly based on 6 major morphoclimatic regions. However, to be biologically meaningful, this typology should fit the distribution patterns of the biological quality elements communities proposed in Water Framework Directive under the lowest possible human pressure. This study aimed to identify and characterize fish-based geographical groups for continental Portugal and their environmental and geographical discriptors, using taxonomic and functional traits. Sampling took place between 2004 and 2006 during Spring. Fish fauna from 155 reference sites was analysed using a multivariate approach. Cluster Analysis on fish composition identified 10 fish-groups, expressing a clear correspondence to the river basin level, due to the restrict basin distribution of many species. Groups showed a wider aggregation in 4 regions with a larger geographical correspondence, statistically supported by Similarity Analysis, both on fish composition and mostly on fish metrics/guilds. Principal Components Analysis revealed major environmental drivers associated to fish-groups and fish-regions. Fish-groups were hierarchically grouped over major and local regions, expressing a large-scale response to a North-South environmental gradient defined by temperature, precipitation, mineralization and altitude, and a regional scale response mainly to drainage area and flow discharge. From North to South, fish-regions were related to the morphoclimatic regions. Results contributed to reduce redundance in abiotic river-types and set the final typology for Portuguese rivers, constituting a fundamental tool for planning and managing water resources.